As relações internacionais e o espaço: análise política da Argentina e do Brasil. - Gomes, Ana Karoline da Silva (Universidade Federal do Tocantins, 2022)
The current course conclusion work addresses the concepts and interaction between outer space and International Relations with a view to South American countries, including Brazil and Argentina. The simple factors of living on a planet, being part of something bigger, and needing the use of satellites daily mean that the objective is to analyze this paradigm under an internationalist vision to reach reflections and inspirations for future objects of study through documentary and systemic analysis. The extra-atmospheric environment involves complete studies, which result from investigations belonging to vast areas of knowledge, such as philosophy, astronomy, and geography. The integration of humanity in terms in which they are allocated to the cosmos establishes circumstances that, added to International Relations, derives in accordance with the historical context, theoretical lines, law, and politics, in which it comprises a unique perspective to the South American States. Latin America has particularities by its very nature, in space this feature permeates, being worth to observe.